The Cajal body marker protein coilin is SUMOylated and possesses SUMO E3 ligase-like activity - Lett, Katheryn E.; McLaurin, Douglas M.; Tucker, Sara K.; Hebert, Michael D. (Frontiers in RNA Research, 2023)
Cajal bodies (CBs) are subnuclear domains that contribute to the biogenesis of several different classes of ribonucleoproteins (RNPs), including small nuclear RNPs. Only some cell types contain abundant CBs, such as neuronal cells and skeletal muscle, but CBs are invariant features of transformed cells. In contrast, coilin, the CB marker protein, is a ubiquitously expressed nuclear protein, but the function of coilin in cell types that lack CBs is not well understood. We have previously shown that coilin promotes microRNA biogenesis by promoting phosphorylation of DGCR8, a component of the microprocessor. Here, we identify seven additional residues of DGCR8 with decreased phosphorylation upon coilin knockdown. In addition to phosphorylation, the addition of a small ubiquitin-like modifier (SUMO) to DGCR8 also increases its stability. Because of coilin’s role in the promotion of DGCR8 phosphorylation, we investigated whether coilin is involved in DGCR8 SUMOylation. We show that coilin knockdown results in global decrease of protein SUMOylation, including decreased DGCR8 and Sp100 (a PML body client protein) SUMOylation and decreased SMN expression. Alternatively, we found that coilin expression rescued Sp100 SUMOylation and increased DGCR8 and SMN levels in a coilin knockout cell line. Furthermore, we found that coilin facilitates RanGAP1 SUMOylation, interacts directly with components of the SUMOylation machinery (Ubc9 and SUMO2), and, itself, is SUMOylated in vitro and in vivo. In summary, we have identified coilin as a regulator of DGCR8 phosphorylation and a promotor of protein SUMOylation with SUMO E3 ligase-like activity.